History of International Relations of Cities of Arkhangelsk Region in 1990s — 2010s: Transition from Social-Humanitarian to Trade-Economic Cooperation - S. Yu. Boldyreva; R. Yu. Boldyreva; A. Yu. Cherednikova (Научный диалог, 2023)
The article discusses the development of international sister city relations in the 1990s — 2010s using the example of the Arkhangelsk region. The authors provide an overview of existing approaches in historiography to analyzing municipal-level international partnership relations in different regions of Russia and the world. Based on a wide range of sources, including international agreements, federal and regional regulatory acts, and reporting documentation over the past 30 years, the article pays particular attention to the region’s attempts in the 2000s — 2010s to move from exclusively social-humanitarian cooperation to developing economic ties with partner cities and regions. The real impact of sister city relations on the development of external economic ties in the region is analyzed in detail, as well as changes in the share of countries with which partner relations were established in the overall external trade turnover of the Arkhangelsk region. The authors conclude that there is currently no state regulation of the institution of sister city relations at the federal and regional levels. Such a situation creates serious difficulties for further development of this institution of public diplomacy, expanding the external economic activities of Russian regions, and spreading Russia’s “soft power” in the world.